Occurrence and Toxicity Mechanisms of Perfluorononanoic Acid, Perfluorodecanoic Acid, and Perfluoroundecanoic Acid in Fish: A Review - Emma Ivantsova; Amany Sultan; Christopher J. Martyniuk (Toxics, 2025)
Per- and polyfluoroalkyl substances (PFAS) are used in consumer products and manufacturing. Perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), and perfluoroundecanoic acid (PFUnDA) are long-chain PFAS composed of 9, 10, and 11 carbons, respectively, which exert sublethal toxicity to aquatic species. Here, we review the data regarding the environmental fate and ecotoxicology of these understudied long-chain PFAS in fish. The objectives of this study were to (1) compile the literature to compare physiological or molecular signaling pathways disrupted by PFNA, PFDA, or PFUnDA; and (2) uncover potential biomarkers and pathways of toxicity of longer-chain PFAS using gene ontology computational approaches to shed light on their mechanism of action. Studies show that PFAS have a range of effects on fish, including developmental issues, changes in gene expression, and behavioral modifications. Based on our review, PFNA has been studied more frequently in fish compared to PFDA and PFUnDA; however, longer-chained PFAS are proposed to pose greater toxicity. Based on the computational approach, prominent pathways affected by PFNA include insulin signaling [“Insulin -> CEBPA/CTNNB/FOXA/FOXO”, “Insulin -> STAT Expression Targets”], immune system signaling [“TNF -> STAT Expression Targets”, “IL6 Expression Targets”, and “IL2 Expression Targets”], and growth hormone/prolactin signaling [“GH1/PRLR Expression Targets”, “PRL/GHR -> STAT Expression Targets”, “PRL/PRLR Expression Targets”]. Several transcripts related to cholesterol metabolism were also affected by PFNA. This review summarizes the current knowledge on the distribution, fate, and ecotoxicology of PFNA, PFDA, and PFUnDA in teleost fish, highlighting potential physiological and molecular responses that could aid in assessing long-chain PFAS toxicity in future studies.